BIONOMICS OF APHID, APHIS GOSSYPII GLOVER INFESTING CORIANDER - AHEIBAM RANILA; P. K. BORAD; M. K. KANANI (The Bioscan, 2014)
Studies on the bionomics of Aphis gossypii Glover on coriander were carried out in laboratory condition. The results showed that it passed through four nymphal instars before attaining the adult stage. The oval shaped greenish brown or yellowish brown first instar nymph subsequently changed to yellowish green to bottle green on development. The average developmental periods of first, second, third and fourth nymphal instar were 1.46 ± 0.51, 1.75 ± 0.62, 1.68 ± 0.63 and 1.60 ± 0.64 days, respectively and the total nymphal period was 6.83 ± 1.39 days. The pre-reproductive, reproductive and post-reproductive periods were noted as 1.66 ± 0.47, 8.53 ± 1.97 and 3.53 ± 0.68 days, respectively. Each adult of A. gossypii could produce 11 to 46 nymphs with an average of 30.76 ± 7.61 nymphs. The rate of reproduction was on an average of 3.86 ± 2.87 nymphs per day. The average longevity of adult aphid was 12.01 ± 1.66 days. The generation period ranged from 18.25 ± 2.97 days.